Inégalités et minorisation des identités chez les femmes artistes dans la francophonie canadienne - Robineau, Anne (Nouvelles perspectives en sciences sociales : revue internationale de systémique complexe et d'études relationnelles, 2013)
Even if women artists are wishing for recognition of their work, independently from their gender, language and belonging to a cultural group, their practices conditions are sometimes linked to these statuses. Through a sociodemographic study of French Canadian artists, we will analyze more specifically the data on women artists. We will show that, even if they have a higher education than man, women artists usually are considerably less paid for their services. We will also try to understand if minorization processes of women from professional artistic francophone communities can explain some gender inequalities and how the production of identity discourses (women, francophonie, linguistic minority) reinforce tensions between art and the identity perspective.
Publisher: Prise de parole
Keywords: Artiste; Artists; Canadian Francophonie; femmes; francophonie canadienne; inequalities; inégalités; minorisation; minorization; women